Treatment patterns of antihypertensive fixed‐dose combinations according to age and number of agents prescribed: Retrospective analysis using a Japanese claims database. Issue 11 (21st August 2019) - Ishida, Takayuki; Oh, Akinori; Nishigaki, Nobuhiro; Tsuchihashi, Takuya
Abstract : Aim: To determine the real‐world use of fixed‐dose combinations (FDC) of antihypertensive agents using data collected from a nationwide medical database of acute hospitals in Japan. Methods: We carried out a retrospective analysis of data from the Medical Data Vision database for patients with hypertension who received an antihypertensive drug prescription between April 2014 and March 2015. The prescription rate of antihypertensive FDC were assessed by class, age and according to combinations. Results: In total, data from 59 867 patients aged 70.0 ± 11.9 years (mean ± SD) were analyzed. Patients were prescribed 1.9 ± 1.0 oral antihypertensive agents (mean ± SD). Overall, 58.6% of patients were prescribed two or more antihypertensive agents, and the most frequently prescribed classes were calcium channel blockers (CCB) and angiotensin II receptor blockers (ARB). As the number of concomitant antihypertensive agents prescribed increased, the prescription rate of a CCB + an ARB FDC decreased, whereas the prescription rate of an ARB + a diuretic FDC increased. This trend was the same regardless of age. Of the 12 222 patients who were prescribed a CCB + an ARB, 26.0% received a FDC. In contrast, of the 922 patients prescribed an ARB + a thiazide diuretic, 80.6% received a FDC. Medium doses of both CCB and ARB agents, and low doses of diuretics were the most frequently prescribed for each class. Conclusions: Our analyses show that the real‐world use of FDC varies depending on the combination of agent class and the number of prescriptions; the latter was similar regardless of age. Geriatr Gerontol Int 2019; 19: 1077–1083 .